The Digitalization of medicine supply chain: How to re-aim the shots in the dark? - Peltoniemi, Teijo (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2021)
ABSTRACT Healthcare expenses have been on the rise for decades. One of the key areas contributing to this ever-expanding growth is medicine expenses. Medicines are required to maintain a sustainable health system in a world of aging populations and pandemics. Novel medicines combat diseases previously considered incurable, and medicines help people with chronic conditions to live normal lives. Furthermore, in emerging economies, pharmacies are often the first and only interface to healthcare services, whereby other medical services are scarce or expensive. However, medicines are associated with costs. To maintain a sustainable health system, the growing expenses have to be managed. There are different ways of controlling medicine expenses. In this age of digitalization, when multiple sectors have been disrupted by digital technologies, it can be argued that digital technologies have a role to play in the medicine supply field. This intersection of medicine supply and information systems has been, however, sparsely studied. This thesis seeks to fill this research gap by exploring the medicine supply chain and discovering obstacles and bottlenecks across the chain. The study also intends to identify how information systems and digital technologies can be utilized to remediate the problems and facilitate an efficient medicine supply chain. The research approaches the medicine supply chain arena through the medicine supply chain concept. The supply chain is a highly complex world involving the pharmaceutical industry and the distribution, prescription and dispensing of medicines. This research examines this arena through cases from across the supply chain covered in four separate studies and related articles. The supply chain concept and the scene are set in one of the studies, followed by studies on the digitalization of pharmacies, medicine waste management in hospitals and the digitalization of the plasma derivatives supply chain. The results of this research illustrate that the main role of digital technology in the management of the medicine supply chain relates to managing several information asymmetries across the chain. The key is to increase transparency between various stakeholders in the chain through novel digital solutions. Currently, the supply chain processes are largely based on rules of thumb rather than facts and evidence, and this should be addressed to maintain a sustainable chain and, subsequently, a sustainable health system. TIIVISTELMÄ Terveydenhuollon kulut ovat nousseet vuosikymmenien ajan. Lääkekulut muodostavat merkittävän osan terveysmenoista. Lääkkeitä tarvitaan kestävän terveydenhuoltojärjestelmän ylläpitämiseksi: lääkkeillä voidaan hoitaa aiemmin parantumattomia sairauksia sekä tukea ikääntyvää väestöä. Kehittyvissä talouksissa apteekit ovat usein myös ensimmäinen ja ainoa yhteys terveyspalveluihin. Lääkkeillä ja niiden kehittämisellä on kuitenkin kulunsa ja kestävän terveydenhuollon järjestelmän ylläpitämiseksi onkin kyettävä ymmärtämään ja hallitsemaan lääkekuluja. Lääkekuluja voidaan hallita eri tavoin. Digitalisaatiolla voidaan ajatella olevan tässä myös roolinsa – useat toimialathan ovat muuttuneet merkittävästi digitaalisten ratkaisujen myötä. Digitalisaation ja tietojärjestelmien merkitystä lääkejakelussa ei olla kuitenkaan tutkittu laajasti. Tämän väitöskirjan tarkoituksena on täyttää tätä tutkimusaukkoa perehtyen lääkejakelun prosesseihin, niihin liittyviin esteisiin ja pullonkauloihin sekä digitaalisiin ratkaisuihin, joilla lääkejakelua voidaan tukea ja tehostaa. Tutkimus lähestyy aluetta mallintaen lääkejakeluketjua. Lääkejakeluketju on monimutkainen globaali systeemi, joka kattaa toimijoita mm. lääketeollisuudesta, jakelusta ja logistiikasta, terveydenhuollosta ja vähittäismyynnistä. Tässä tutkimuksessa jakeluketjua tarkastellaan neljän tutkimuksen kautta, jotka liittyvät lääkejakeluketjun eri osiin. Aluksi esitellään lääkejakeluketjukonsepti, jota seuraavat tutkimukset apteekkien digitalisoinnista, sairaalan lääkehuollosta ja veriplasmatuotteiden toimitusketjun digitalisoinnista. Tämän tutkimuksen tulokset havainnollistavat, että digitaalisten ratkaisujen päärooli lääkejakeluketjun hallinnassa liittyy varsinkin informaatiosymmetrioiden hallintaan sekä tiedon avoimuuden ja läpinäkyvyyden lisäämiseen ketjun eri sidosryhmien välillä. Nykyisin lääkejakeluketjun prosesseja leimaa epävarmuus ja faktoihin perustuva päätöksenteko on vaikeaa, mikä heikentää tehokkaan lääkejakelun ylläpitämistä.